2021
DOI: 10.3389/fgeed.2021.717017
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasts: From Isolation to CRISPR/Cas Genome Editing Application

Abstract: In the clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR associated protein (Cas) system, protoplasts are not only useful for rapidly validating the mutagenesis efficiency of various RNA-guided endonucleases, promoters, sgRNA designs, or Cas proteins, but can also be a platform for DNA-free gene editing. To date, the latter approach has been applied to numerous crops, particularly those with complex genomes, a long juvenile period, a tendency for heterosis, and/or self-incompatibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Plant “protoplasts” (whose name originates from the ancient Greek prōtóplastos, meaning “first-formed”) are whole plant cells without cell walls, and have been widely used in plant science research and crop breeding. Protoplast transformation/transfection involves the direct delivery of plasmid DNA to individual protoplasts using polyethylene glycol (PEG), electroporation or other methods [ 155 ]. Protoplast transformation has several benefits, including: delivery of multiple plasmids with high levels of cotransformation, no binary vector required, and providing the ability to check CRISPR construct efficiency in a short time.…”
Section: Enabling Technologiesmentioning
confidence: 99%
“…Plant “protoplasts” (whose name originates from the ancient Greek prōtóplastos, meaning “first-formed”) are whole plant cells without cell walls, and have been widely used in plant science research and crop breeding. Protoplast transformation/transfection involves the direct delivery of plasmid DNA to individual protoplasts using polyethylene glycol (PEG), electroporation or other methods [ 155 ]. Protoplast transformation has several benefits, including: delivery of multiple plasmids with high levels of cotransformation, no binary vector required, and providing the ability to check CRISPR construct efficiency in a short time.…”
Section: Enabling Technologiesmentioning
confidence: 99%
“…Another topic commonly associated with genome editing and CRISPR tools is using protoplasts (plant cells without cell walls) as a rapid validation system. It provides a platform to test the mutagenesis efficiency of RNA-guided endonucleases, promoters, sgRNA designs, or Cas proteins before the full-scale transformation in the host plant [131]. The popularity of this approach is reflected in the network map in which the keyword "protoplast" is present near "site-directed mutagenesis", "crispr/cas", and "transgene" nodes.…”
Section: Vosviewer Bibliometric Analysismentioning
confidence: 99%
“…Surprisingly, Andersson et al (2018) reported that a large proportion of the regenerated plants contained inserts at the target site, containing either random fragments of potato chromosomal DNA or originating from the DNA template used to synthesize the gRNA. Despite the success of PEG-mediated delivery of RNPs in certain transformation-recalcitrant species, few plant species have been satisfactorily regenerated from protoplasts ( Yue et al, 2021 ). Moreover, genome instability caused by protoplast regeneration is not infrequent ( Fossi et al, 2019 ).…”
Section: Ribonucleoproteinsmentioning
confidence: 99%
“…Moreover, genome instability caused by protoplast regeneration is not infrequent ( Fossi et al, 2019 ). Due to a lack of well-established and species-specific protoplast isolation and regeneration techniques, especially for monocotyledonous plants, the adoption of PEG-mediated RNP genome editing has been limited thus far ( Yue et al, 2021 ). Other useful strategies for the delivery of genes or proteins to mammalian cells, such as electroporation and lipofection, have also been tested in plants.…”
Section: Ribonucleoproteinsmentioning
confidence: 99%